PEMERIKSAAN KESEHATAN BAGI PENYANDANG DISABILITAS DI KABUPATEN GARUT - Hasbi Taobah Ramdani; Gina Nafsa Mutmainna; Naning Suryani (Jurnal Pengabdian Masyarakat DEDIKASI, 2021)
Persons with disabilities are any person who experiences physical, intellectual, mental, and/or sensory limitations in the long term who in interacting with the environment may experience obstacles and difficulties to participate fully and effectively with other citizens based on equal rights, one of which is the right to obtain information and communication that is easily accessible in health services, to obtain equality and opportunity to access resources in the health sector and to obtain equality and opportunity for safe, quality, and affordable health services. The method of implementing this community service activity is through health counseling and health checks such as blood pressure, blood sugar, uric acid and cholesterol which are located at the PPDI Secretariat of Garut Regency with 24 participants attending. The results of this activity showed that the participants were enthusiastic about participating in the activity, besides that the participants knew about the general condition seen from the results of the examination.